Conceptual Metaphors in Basketball Discourse - Toleikienė, Reda; Būdvytytė-Gudienė, Aina (Respectus Philologicus, 2013)
This article presents part of the research performed within the scope of the national project “Conceptual Metaphors in Public Discourse,”1 financed by the Research Council of Lithuania. The aim of the present paper is to analyze conceptual metaphors in the discourse of the European Basketball Championship which took place in Kaunas, Lithuania in 2011, as well as to determine the source concepts. The analysis allows certain features of the images which are used while conceptualizing the entities related to basketball to be described. The metaphorical collocations drawn from the Lithuanian language corpora and web portals (www.delfi.lt and www.lrytas.lt) were selected and analyzed from 31 August 2011 to 18 September 2011. A conceptual metaphor is defined as an interaction of two conceptual fields (source and target concepts). On the basis of the analyzed conceptual sayings, the reconstructed conceptual metaphors proved that the most prolific metaphors are of war, ontology, and scale. In basketball discourse, the war metaphor is characterized by the fact that the image of sport is war is supplemented by other source concepts (e.g.,a person, a building, a thing, a material, a scale). The features of two or sometimes even three source concepts are ascribed to the target concept.
Keywords: Conceptual Metaphor; Source Concept; Target Concept